Atomic Layer Deposition of ZnO on CuO Enables Selective and Efficient Electroreduction of Carbon Dioxide to Liquid Fuels. Issue 42 (10th September 2019) - Ren, Dan; Gao, Jing; Pan, Linfeng; Wang, Zaiwei; Luo, Jingshan; Zakeeruddin, Shaik M.; Hagfeldt, Anders; Grätzel, Michael
Abstract: Electrochemical reduction of carbon dioxide, if powered by renewable electricity, could serve as a sustainable technology for carbon recycling and energy storage. Among all the products, ethanol is an attractive liquid fuel. However, the maximum faradaic efficiency of ethanol is only ≈10 % on polycrystalline Cu. Here, CuZn bimetallic catalysts were synthesized by in situ electrochemical reduction of ZnO‐shell/CuO‐core bi‐metal‐oxide. Dynamic evolution of catalyst was revealed by STEM‐EDS mapping, showing the migration of Zn atom and blending between Cu and Zn. CuZn bimetallic catalysts showed preference towards ethanol formation, with the ratio of ethanol/ethylene increasing over five times regardless of applied potential. We achieved 41 % faradaic efficiency for C2+ liquids with this catalyst. Transitioning from H‐cell to an electrochemical flow cell, we achieved 48.6 % faradaic efficiency and −97 mA cm −2 partial current density for C2+ liquids at only −0.68 V versus reversible hydrogen electrode in 1 m KOH. Operando Raman spectroscopy showed that CO binding on Cu sites was modified by Zn. Free CO and adsorbed *CH3 are believed to combine and form *COCH3 intermediate, which is exclusively reduced to ethanol. Abstract : Bimetallic catalysis : Using atomic layer modification of CuO by ZnO, in situ reduced CuZn nanowires are prepared as selective catalysts for CO2 electroreduction to ethanol. The excessive CO formation catalyzed by Zn and the fast kinetics of *CH3 formation at high overpotential on Cu are believed to be critical in determining the selectivity of ethanol.